2014
DOI: 10.1038/aps.2013.185
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin inhibits angiotensin II-induced cardiac hypertrophy via the redox-sensitive ERK1/2, p38 and NF-κB pathways

Abstract: Pue attenuates Ang II-induced cardiac hypertrophy by inhibiting activation of the redox-sensitive ERK1/2, p38 and the NF-κB pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 35 publications
0
38
0
Order By: Relevance
“…Accumulated data show that CMs are remodeled or "dedifferentiated" in pathological conditions, i.e. heart failure and other cardiovascular diseases, presenting enhanced proliferation ability and morphological and functional properties similar to embryonic CMs [10,11]. Based on the myocardial protection effects of puerarin reported previously, we hypothesized that puerarin might also inhibit CM proliferation, thus further support its potential effect on reversing cardiac phenotypic remodeling in heart diseases.…”
Section: Introductionmentioning
confidence: 62%
“…Accumulated data show that CMs are remodeled or "dedifferentiated" in pathological conditions, i.e. heart failure and other cardiovascular diseases, presenting enhanced proliferation ability and morphological and functional properties similar to embryonic CMs [10,11]. Based on the myocardial protection effects of puerarin reported previously, we hypothesized that puerarin might also inhibit CM proliferation, thus further support its potential effect on reversing cardiac phenotypic remodeling in heart diseases.…”
Section: Introductionmentioning
confidence: 62%
“…Moreover, previous reports have established a significant role of the ERK pathway to hypertrophic gene expression induced by hypertrophic agonists using an MEK-1 specific inhibitor and cDNA gene expression profiling in cardiac myocytes [64,65]. In another study it was reported that Ang II-induced CH by activation of the redox-sensitive ERK1/2, p38, and the NF-κB pathways in C57BL/6J mice which is attenuated by Pue, an isoflavone polyphenolic antioxidant [66].…”
Section: Discussionmentioning
confidence: 96%
“…This G␣ 13 -initiated cascade is independent of ANG II-activated G␣ q/11 signaling that was earlier linked to pathological cardiac hypertrophy (1143). RhoA is also a downstream effector of Nox-induced ROS in response to ANG II treatment (49,746), as are various redox-sensitive kinases and transcription factors linked to cardiac hypertrophy (148,567,1107).…”
Section: Ang II In Cardiac Hypertrophymentioning
confidence: 94%